Carbazole-functionalized hyper-cross-linked polymers for CO2 uptake based on Friedel–Crafts polymerization on 9-phenylcarbazole - Fang, Dandan; Li, Xiaodong; Zou, Meishuai; Guo, Xiaoyan; Zhang, Aijuan (Beilstein Journal of Organic Chemistry, 2019)
To systematically explore the effects of the synthesis conditions on the porosity of hyper-cross-linked polymers (HCPs), a series of 9-phenylcarbazole (9-PCz) HCPs (P1–P11) has been made by changing the molar ratio of cross-linker to monomer, the reaction temperature T1, the used amount of catalyst and the concentration of reactants. Fourier transform infrared spectroscopy was utilized to characterize the structure of the obtained polymers. The TG analysis of the HCPs showed good thermal stability. More importantly, a comparative study on the porosity revealed that: the molar ratio of cross-linker to monomer was the main influence factor of the BET specific surface area. Increasing the reaction temperature T1 or changing the used amount of catalyst could improve the total pore volume greatly but sacrificed a part of the BET specific surface area. Fortunately changing the concentration of reactants could remedy this situation. Slightly changing the concentration of reactants could simultaneously obtain a high surface area and a high total pore volume. The BET specific surface areas of P3 was up to 769 m2 g−1 with narrow pore size distribution and the CO2 adsorption capacity of P11 was up to 52.4 cm3 g−1 (273 K/1.00 bar).
Keywords: 9-phenylcarbazole; CO2 uptake; Friedel–Crafts polymerization; hyper-cross-linked polymers; microporous

(untitled) - Li, B.; Guan, Z.; Wang, W.; Yang, X.; Hu, J.; Tan, B.; Li, T. (Adv. Mater. (Weinheim, Ger.), 2012)

(untitled) - Sekerová, L.; Lhotka, M.; Vyskočilová, E.; Faukner, T.; Slováková, E.; Brus, J.; Červený, L.; Sedláček, J. (Chem. – Eur. J., 2018)

(untitled) - Chaoui, N.; Trunk, M.; Dawson, R.; Schmidt, J.; Thomas, A. (Chem. Soc. Rev., 2017)

(untitled) - Xu, C.; Wang, H.; Wang, Q.; Wang, Y.; Zhang, Y.; Fan, G. (Appl. Surf. Sci., 2019)

(untitled) - Liang, H.-P.; Chen, Q.; Han, B.-H. (ACS Catal., 2018)

(untitled) - Zhang, W.; Tang, J.; Yu, W.; Huang, Q.; Fu, Y.; Kuang, G.; Pan, C.; Yu, G. (ACS Catal., 2018)

(untitled) - Zhai, T.-L.; Tan, L.; Luo, Y.; Liu, J.-M.; Tan, B.; Yang, X.-L.; Xu, H.-B.; Zhang, C. (Chem. – Asian J., 2016)

(untitled) - Wang, X.; Zhao, Y.; Wei, L.; Zhang, C.; Yang, X.; Yu, M.; Jiang, J.-X. (Macromol. Chem. Phys., 2015)

(untitled) - Deka, N.; Barman, J.; Deka, J.; Raidongia, K.; Dutta, G. K. (ChemElectroChem, 2019)

(untitled) - Dawson, R.; Stevens, L. A.; Drage, T. C.; Snape, C. E.; Smith, M. W.; Adams, D. J.; Cooper, A. I. (J. Am. Chem. Soc., 2012)

(untitled) - Zhu, X.; Tian, C.; Jin, T.; Browning, K. L.; Sacci, R. L.; Veith, G. M.; Dai, S. (ACS Macro Lett., 2017)

(untitled) - Hou, S.; Tan, B. (Macromolecules, 2018)

(untitled) - Zhu, T.; Xie, F.; Huang, T.; Tian, K.; Wu, Z.; Yang, H.; Li, L. (ACS Macro Lett., 2018)

(untitled) - Hou, S.; Razzaque, S.; Tan, B. (Polym. Chem., 2019)

(untitled) - Li, B.; Gong, R.; Wang, W.; Huang, X.; Zhang, W.; Li, H.; Hu, C.; Tan, B. (Macromolecules, 2011)

(untitled) - Zhang, C.; Zhu, P.-C.; Tan, L.; Liu, J.-M.; Tan, B.; Yang, X.-L.; Xu, H.-B. (Macromolecules, 2015)

(untitled) - Song, K.; Zou, Z.; Wang, D.; Tan, B.; Wang, J.; Chen, J.; Li, T. (J. Phys. Chem. C, 2016)

(untitled) - Saleh, M.; Lee, H. M.; Kemp, K. C.; Kim, K. S. (ACS Appl. Mater. Interfaces, 2014)

(untitled) - Chen, Q.; Liu, D.-P.; Luo, M.; Feng, L.-J.; Zhao, Y.-C.; Han, B.-H. (Small, 2014)

(untitled) - Zhang, X.; Lu, J.; Zhang, J. (Chem. Mater., 2014)

(untitled) - Jiang, F.; Jin, T.; Zhu, X.; Tian, Z.; Do-Thanh, C.-L.; Hu, J.; Jiang, D.-e.; Wang, H.; Liu, H.; Dai, S. (Macromolecules, 2016)

(untitled) - Luo, J.; Zhang, X.; Zhang, J. (ACS Catal., 2015)

(untitled) - Jin, T.; Xiong, Y.; Zhu, X.; Tian, Z.; Tao, D.-J.; Hu, J.; Jiang, D.-e.; Wang, H.; Liu, H.; Dai, S. (Chem. Commun., 2016)

(untitled) - Yuan, Y.; Huang, H.; Chen, L.; Chen, Y. (Macromolecules, 2017)

(untitled) - Zhang, R.-R.; Yin, Q.; Liang, H.-P.; Chen, Q.; Luo, W.-H.; Han, B.-H. (Polymer, 2018)

(untitled) - Qiao, S.; Li, Z.; Zhang, B.; Li, Q.; Jin, W.; Zhang, Y.; Wang, W.; Li, Q.; Liu, X. (Microporous Mesoporous Mater., 2019)

(untitled) - Yin, Q.; Chen, Q.; Lu, L.-C.; Han, B.-H. (Beilstein J. Org. Chem., 2017)

(untitled) - Wang, T.; Zhao, Y.-C.; Zhang, L.-M.; Cui, Y.; Zhang, C.-S.; Han, B.-H. (Beilstein J. Org. Chem., 2017)

(untitled) - Thirion, D.; Lee, J. S.; Özdemir, E.; Yavuz, C. T. (Beilstein J. Org. Chem., 2016)

(untitled) - Samanta, P.; Chandra, P.; Ghosh, S. K. (Beilstein J. Org. Chem., 2016)

(untitled) - Lang, M.; Schade, A.; Bräse, S. (Beilstein J. Org. Chem., 2016)

(untitled) - Cantín, Á.; Gomez, M. V.; de la Hoz, A. (Beilstein J. Org. Chem., 2016)

(untitled) - Zhu, J.-H.; Chen, Q.; Sui, Z.-Y.; Pan, L.; Yu, J.; Han, B.-H. (J. Mater. Chem. A, 2014)

(untitled) - Zhang, B.; Yan, J.; Li, G.; Wang, Z. (Polym. Chem., 2019)

(untitled) - Su, H.; Du, Y.; Zhang, J.; Peng, P.; Li, S.; Chen, P.; Gozin, M.; Pang, S. (ACS Appl. Mater. Interfaces, 2018)

(untitled) - Sing, K. S. W. (Pure Appl. Chem., 1985)

(untitled) - Zhou, J.-X.; Luo, X.-S.; Liu, X.; Qiao, Y.; Wang, P.; Mecerreyes, D.; Bogliotti, N.; Chen, S.-L.; Huang, M.-H. (J. Mater. Chem. A, 2018)

(untitled) - Fu, H.-X.; Zhang, Z.-H.; Fan, W.; Wang, S.; Liu, Y.; Huang, M.-H. (J. Mater. Chem. A, 2019)

(untitled) - Zhang, A.; Gao, H.; Li, W.; Bai, H.; Wu, S.; Zeng, Y.; Cui, W.; Zhou, X.; Li, L. (Polymer, 2016)

(untitled) - Deka, N.; Deka, J.; Dutta, G. K. (ChemistrySelect, 2018)

(untitled) - Yao, C.; Cui, D.; Zhu, Y.; Xie, W.; Zhang, S.; Xu, G.; Xu, Y. (New J. Chem., 2019)

(untitled) - Xiong, S.; Tang, X.; Pan, C.; Li, L.; Tang, J.; Yu, G. (ACS Appl. Mater. Interfaces, 2019)

(untitled) - Zhi, Y.; Yao, Z.; Jiang, W.; Xia, H.; Shi, Z.; Mu, Y.; Liu, X. (ACS Appl. Mater. Interfaces, 2019)

(untitled) - Gu, C.; Bao, Y.; Huang, W.; Liu, D.; Yang, R. (Macromol. Chem. Phys., 2016)

(untitled) - Xiang, Z.; Mercado, R.; Huck, J. M.; Wang, H.; Guo, Z.; Wang, W.; Cao, D.; Haranczyk, M.; Smit, B. (J. Am. Chem. Soc., 2015)

(untitled) - Madani, S. H.; Rodríguez-Reinoso, F.; Biggs, M. J.; Pendleton, P. (J. Chem. Eng. Data, 2018)